Exercise, Telomeres, and Cancer: “The Exercise-Telomere Hypothesis” - Nomikos, Nikitas N.; Nikolaidis, Pantelis T.; Sousa, Caio V.; Papalois, Apostolos E.; Rosemann, Thomas; Knechtle, Beat (Frontiers in Physiology, 2018)
This review aims to identify and analyse the crucial role of physical activity (PA) and exercise against cancer and aging. The review of literature substantially proved that exercise via mechanisms and a series of metabolic phenomena is crucial for the sustainability of Telomere Length (TL). According to scientific data, exercise has a key role on achieving higher TL and regulates telomerase activity. The “Exercise-telomere hypothesis”, E.T.H., is presented analytically in the current manuscript. The findings of the manuscript will contribute to the adoption of the term E.T.H., and will inspire a number of preventative-therapeutic strategies that will be based on the role of exercise against cancer and aging. The TL is one of the indicators of total human health. The “Exercise-telomere hypothesis”, would be one of the fundamental principles of the global health initiatives, such as Exercise is Medicine® (EIM). The deep knowledge of the way exercise affects the enzyme of telomerase and telomere, will reveal the potential value of exercise for the sustainability of the telomere. Exercise, rest, mental health and nutrition are the key factors for longevity and well-being. The sustainability of the length and quality of telomeres will be one of the leading search priorities of medicine and sports science in the future. Further research is needed to reveal the mechanisms with which exercise contributes to achieving a telomere of high quality and length.